Manifestations of Latgalian Self-awareness in Emigration in Western Countries after the Second World War - Malahovskis, Vladislavs (Acta humanitarica academiae Saulensis, 2025)
The article deals with some aspects of Latgalian identity and perception in emigration, their origin and the key issues. At the end of the Second World War about 120,000 –140,000 residents of Latvia found their asylum in the West. About 7,000 of them were Latgalians. Despite their common sense of belonging to the lost Latvia, common aspiration for freedom and an independence of Latvian state, the Latvian intelligentsia was not united in emigration. It was composed of different social and scientific organizations, etc. The lack of unity is based on historical heritage and stereotypes. Historically, various socio-economic circumstances have formed in Latgale, different development of sociopolitical events and then the formation of national consciousness. Even after the creation of an independent state (1918), Latvians still lacked a unified national awareness. The Latvians of Latgale (Latgalians) were often treated as contrasted to other Latvians – the “Balts”. However, Latgalians in emigration were not united. Their beliefs were very different in a number of issues: 1. The written language and the language of worship (Latvian or Latgalian). Representatives of the Catholic Church in emigration believed that services should be conducted in the Latvian language, as there were Catholics among Latvians, and some Latgalians believed that services should be conducted only in Latgalian; 2. The historical concept (authoritarian regime of Karlis Ulmanis and Latgale). Some sharply criticized Karlis Ulmanis for the restriction of the Latgalian language and literature in the second half of the 30s of the 20th century, whilst others supported his economic policy and other activities in favour of Latgale. The most active and important organizations that defended everything Latgalian were Vladislavs Locis Publishing House and Latgale Resarch Institute (LRI). The main issue and at the same time the problem was why the continuity of these selfless efforts disappeared already in the second generation of emigrants? Understanding of the Latgalian self-awareness in the first generation of the Latgalian emigration was largely reduced only to the use of the Latgalian language. Unlike Latvians from other regions, who saw in the Latvian life quite broad prospects for their activities, the Latgalian language and literature seemed a narrow and unpromising sphere to the new generation of Latgalian emigrants. However, the continuity, to a greater or lesser extent, was preserved after the restoration of Latvia’s independence. In 1991, with the official consent and with the support of the members of the Latgale Research Institute, who were in emigration, it was decided to continue the work of the Institute in Daugavpils. Currently, the Latgale Research Institute is the branch of Daugavpils University. Latgale Cultural Centre Publishing House continues traditions started by V. Locis in Rezekne.